Instructor's solution manual: Sears& Zemansky'sUniversity Physics. - Anderson, W. Wayne, Anderson (Hudson: Pearson, 2020)
Practice makes perfect. The new 15th Edition of University Physics with Modern Physics draws on a wealth of data insights from hundreds of faculty and thousands of student users to address one of the biggest challenges for students in introductory physics courses: seeing patterns and making connections between problem types. Students learn to recognize when to use similar steps in solving the same problem type and develop an understanding for problem solving approaches, rather than simply plugging in an equation.